OPTIMASI FORMULASI SIRUP FRAKSI TIDAK LARUT ETIL ASETAT YANG MENGANDUNG ALKALOID DARI BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis L.) - Mimiek Murrukmihadi; Subagus Wahyuono; Marchaban Marchaban; Sudibyo Martono (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
Ethylacetate insoluble fraction containing alkaloids from the hibiscus flower (Hibiscus rosa-sinensis L.) with a concentration of 0.6% w/v has mucolityc activity which is equivalent to 0.1% acetylcysteine based on the capasity to decrease viscosity of the mucus. The use of hibiscus as a new cough medicine done traditionally. Syrup of ethylacetate insoluble fraction containing alkaloids was the appropiate liquid dosage form that has some advantages for examples easy to use and fast absorption of the active substance. The study aims to determine the optimum formulation syrup ethanolic fractions containing alkaloids from hibiscus flowers using the method of Simplex Lattice Design. Ethylacetate insoluble fraction containing alkaloids from the hibiscus flower is obtained by using the Vacuum Liquid Chromatography (VLC). Simplex Lattice Design Methods used to optimize the formulation syrup ethylacetate insoluble fraction containing alkaloids from hibiscus flower with seven formulas with variations in the amount of glycerin, sorbitol solution 70%, and mucilago 0.5% CMC-Na. Physical stability was analized to find higher total response value (R total) as parameter of the optimum formula by Simplex Lattice Design Methods with Design Expert ® software version 8.0.2. Optimum formula syrup ethylacetate insoluble fraction containing alkaloids from the hibiscus flower obtained with the proportion of 25.376% glycerine, 51.985% of 70% sorbitol solution, and 22.639% of 0.5% CMC Na mucilago. Data obtained physical characteristics test compared with prediction value using Design Expert ® software version 8.0.2. Physical characteristics of optimum syrup ad the zero week compared with physical characteristics on the forth week using paired t-test. The result showed that physical properties of syrup formula optimum didn’t different significantly for easy for pouring and tasted response except for viscosity and acidity. Ethylacetate fraction syrup containing alkaloids from hibiscus flower optimization results are less stable during the four weeks of storage.